Makanan Halal Pada Destinasi Wisata di Nusa Tenggara Barat - Siti Hasanah; Fitriani Amelia; Yulias Erwin (IJECA (International Journal of Education and Curriculum Application), 2018)
The term halal roots from Islamic faith based on the teaching of Quran and Sunnah. This concept has recently been embraced in the management of tourism worldwide, including one in Indonesia province of West Nusa Tenggara. Halal brand attached to food products provided at tourist destinations tend to be seen from the aspect of ingredients while neglecting the aspect of processing. In fact, both aspects are inseparable in determining whether or not a product is halal according to Islamic law or sharia. This paper aims to explore processing standard of halal food at tourist destinations in West Nusa Tenggara and compare the processing with that of Islamic sharia. Comparative method was used to compare the standardization of halal food available at tourist destinations and the standardization based on sharia. The findings indicate that practice of halal tourism in West Nusa Tenggara increases evidenced in the increase of Moslem travelers visiting this province. However, the processing of food and beverages need to improve in order to comply with sharia standard as there are a number of hotels and restaurants in the region that have yet to receive a halal certificate from the authority, in this case the Indonesian Board of Islamic Scholars (MUI).